3D face modeling from single image based on discrete shape space. (13th September 2020) - Zhang, Dan; Lv, Chenlei; Liu, Na; Wu, Zhongke; Wang, Xingce
Abstract: In this article, we propose a novel 3D face modeling method which constructs a new 3D face model from a low‐dimensional feature space consisted of a large set of blend shapes based on the discrete shape space theory. The details of original face features are completely retained during the modeling process and a large number of new natural faces are constructed by several face samples. The optimization process of our method is independently decoupled for different facial attributes (identity, expression, and head pose), which improves the application flexibility and reduces the probability of it falling into a local optimal situation. The new facial data with new attributes are constructed based on the geodesic path search in discrete shape space with sufficient freedom and accuracy. In experiments and applications based on public databases (Helen, LFW, and CUFS), the modeling results show our method can provide high‐quality 3D face model, with enough freedom for face expression editing and natural facial expression animation from a small facial sample set. Abstract : (1) We construct a discrete shape space to represent 3D faces by facial landmarks for face representation, similarity measurement, and new face synthesis without complicated preprocessing. (2) We propose a new optimization process to match a 3D face counterpart and 2D facial image in the discrete shape space. (3) We propose an effective 3D face data synthesis method based on the optimization process which determines the necessary parameters from the geodesic path searching in discrete shape space.